2001
DOI: 10.1111/j.1749-6632.2001.tb05786.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychostimulants in the Treatment of Adults with Psychosis and Attention Deficit Disorder

Abstract: Whether conceptualized as comorbid ADD with psychosis or as a distinct diagnostic entity—ADD psychosis—patients with features of both ADD and psychosis benefit from treatment with psychostimulants. It is hypothesized that psychostimulants have their therapeutic effect via amelioration of frontal lobe dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Interestingly, case reports on ADHD and comorbid neuroleptic-refractory adult-onset psychosis presenting with delusions and hallucinations observed improvement of schizophrenic symptoms when adding psychostimulants to ongoing antipsychotic treatment and even after withdrawal of the antipsychotics (Pine et al, 1994). It has been suggested that ADHD psychosis favourably responding to psychostimulants constitutes a distinct entity with key symptoms like brief hallucinations, delusions with evident compensatory functions concerning low self-esteem, poor impulse control, aggression and impaired judgement whereas interest in social life maintains and disorganization of thoughts is rare (Opler et al, 2001). Psychotic symptoms usually disappear quickly after administration of psychostimulants, however, long-term prognosis of recurring psychotic episodes and social adjustment is poor (ibid.).…”
Section: Adhdmentioning
confidence: 97%
“…Interestingly, case reports on ADHD and comorbid neuroleptic-refractory adult-onset psychosis presenting with delusions and hallucinations observed improvement of schizophrenic symptoms when adding psychostimulants to ongoing antipsychotic treatment and even after withdrawal of the antipsychotics (Pine et al, 1994). It has been suggested that ADHD psychosis favourably responding to psychostimulants constitutes a distinct entity with key symptoms like brief hallucinations, delusions with evident compensatory functions concerning low self-esteem, poor impulse control, aggression and impaired judgement whereas interest in social life maintains and disorganization of thoughts is rare (Opler et al, 2001). Psychotic symptoms usually disappear quickly after administration of psychostimulants, however, long-term prognosis of recurring psychotic episodes and social adjustment is poor (ibid.).…”
Section: Adhdmentioning
confidence: 97%
“…The cited studies show no worsening of psychotic symptoms but an amelioration of both attentional deficits and psychotic symptoms, probably by increasing perfusion to the frontal lobes [112] .…”
Section: Environmental Risk Factorsmentioning
confidence: 99%
“…In fact, there are case studies demonstrating that stimulants have been well tolerated in subjects with psychosis, with or without concomitant antipsychotic treatment [105109] , with positive effects on cognition [110,111] . It has been suggested that the positive effect of methylphenidate, described in some studies, may be due to a regulation of frontal hypodopaminergic state [110,112] . In fact, methylphenidate affects dopamine D1 receptors in frontal regions improving cognition, whereas antipsychotics block D2 receptors in mesolimbic systems, without influencing D1 receptors [110] .…”
Section: Stimulants and Psychosismentioning
confidence: 99%
See 1 more Smart Citation
“…Though an addictive compound, amphetamine (AMPH) is a drug that has been used to treat a variety of diseases such as narcolepsy, obesity and ADHD [1,2]. Initially described as a potent sympathomimetic drug with cardiovascular and gastro-enteric effects, it soon became clear that AMPH has reinforcing properties leading to widespread abuse [3].…”
Section: Introductionmentioning
confidence: 99%